2, 2′‐[(Disulfanediyl)bis{5‐[(1E)‐(2‐hydroxybenzylidene)amino]‐1, 3‐thiazole‐4, 2‐diyl}]diphenol: synthesis, crystal structure and calculation of molecular hyperpolarizability. Issue 8 (6th July 2017) - Zarei, Seyed Amir; Piltan, Mohammad; Mashhun, Asmar; Rudbari, Hadi Amiri; Bruno, Giuseppe
Abstract : The synthesis and crystal structure of a novel Schiff base compound obtained from salicylaldehyde and dithiooxamide has been investigated. A one‐dimensional chain is formed along the b axis via double intermolecular C—H…S hydrogen bonds. DFT calculations have allowed the molecular hyperpolarizability to be evaluated. Abstract : The title Schiff base compound {systematic name: 2‐[5‐[( E )‐(2‐hydroxybenzylidene)amino]‐4‐(2‐{5‐[( E )‐(2‐hydroxybenzylidene)amino]‐2‐(2‐hydroxyphenyl)‐1, 3‐thiazol‐4‐yl}disulfanyl)‐1, 3‐thiazol‐2‐yl]phenol}, C32 H22 N4 O4 S4, incorporating a disulfanediyl (dithio) linkage, was obtained from the condensation reaction between two equivalents of salicylaldehyde and one equivalent of dithiooxamide in dimethylformamide, and was characterized by elemental analysis, IR spectroscopic analysis and single‐crystal X‐ray diffraction. A one‐dimensional chain is formed along the b axis via double intermolecular C—H…S hydrogen bonds. The HOMO (highest occupied molecular orbital) and LUMO (lowest unoccupied molecular orbital) energies and some related molecular parameters were calculated at the B3LYP/6‐311G(d, p) level of theory. The molecular hyperpolarizability was also calculated.